Effectiveness of Foot Exercise Intervention in Stabilizing Blood Glucose Levels in Patients with Type 2 Diabetes Mellitus in the Internal Medicine Room of Blambangan Hospital in 2025: Case Study - Anita Dwi Ariyani; Farhan, Muhammad Hisyam; Efendi, Achmad (Jurnal Keperawatan Muhammadiyah, 2026)
Background: Diabetes mellitus is a chronic metabolic disorder characterized by elevated blood glucose levels due to insufficient insulin production or ineffective insulin utilization. Persistent hyperglycemia can lead to serious acute and chronic complications. One non-pharmacological approach to help reduce blood glucose levels is physical activity, such as foot exercises. Foot exercises are simple, easy to perform, do not require special equipment, and can be practiced independently by patients with type 2 diabetes mellitus. Objective: To determine the effect of foot exercise intervention on blood glucose levels in a type 2 diabetes mellitus patient with the nursing problem of blood glucose imbalance in the internal medicine ward of RSUD Blambangan Banyuwangi. Methods: This scientific paper is structured as a case study using the nursing care approach, which includes assessment, nursing diagnosis, planning, implementation, and evaluation. The non-pharmacological intervention consisted of foot exercises performed for three consecutive days, with blood glucose levels measured before and after the intervention. Result: After performing foot exercises for three consecutive days, the patient's blood glucose level decreased significantly from 316 mg/dL to 124 mg/dL. This result indicates that the foot exercise intervention had a positive effect on blood glucose stabilization. Conclusion: : Foot exercise is proven to be an effective, simple, and easily applicable non- pharmacological intervention to help reduce blood glucose levels in patients with type 2 diabetes mellitus. This intervention can serve as a supportive therapy in the management of hyperglycemia.